Ursodeoxycholic acid improves muscle contractility and inflammation in symptomatic gallbladders with cholesterol gallstones. Issue 6 (21st December 2006) - Guarino, Michele Pier Luca; Cong, Ping; Cicala, Michele; Alloni, Rossana; Carotti, Simone; Behar, Jose
Abstract : Objective: To examine the mechanisms of action of ursodeoxycholic acid (UDCA) on gallbladder (GB) muscle cells in patients with symptomatic cholesterol gallstones (GSs) as it reduces the incidence of acute cholecystitis. Design and patients: A double-blind study was performed on 15 patients, 7 randomised to UDCA and 8 to placebo, treated for 4 weeks before cholecystectomy. Muscle contraction induced by cholecystokinin (CCK)-8, acetylcholine (ACh) and potassium chloride (KCl) was determined in enzymatically isolated GB muscle cells, and cholesterol levels were determined in plasma membranes. H2 O2, lipid peroxidation, platelet-activating factor (PAF)-like lipids, prostaglandin E2 (PGE2 ) and catalase activity were determined as biochemical markers of oxidative stress and inflammation in muscle cells. Results: UDCA significantly increased GB muscle cell contraction induced by all concentrations of CCK-8, ACh and KCl, and reduced the plasma membrane cholesterol (mean (SD) 0.32 (0.16) vs 0.72 (0.5) μmol/mg of protein) compared with placebo. In GB muscle cells, UDCA treatment significantly decreased the levels of H2 O2 (4.4 (1.9) vs 13.7 (5.3) μmol/mg of protein), lipid peroxidation (malondialdehyde levels 1.3 (0.4) vs 2.52 (0.7) nmol/100 mg of protein), PAF-like lipids (8.9 (4.9) vs 29.6 (7.1) pg/mg of protein) as well as the production of PGE2 (142 (47) vs 365 (125) pg/mg of protein) and catalase activity (14.5 (9.4) vs 35.8 (12.7) units/mg of protein) when compared with placebo. Conclusion: These studies suggest that UDCA treatment improves GB muscle contractility by decreasing the cholesterol content in the plasma membrane of muscle cells, and the biochemical parameters of oxidative stress, thus explaining its possible therapeutic mechanisms in patients with symptoms of cholesterol GSs.